2000
DOI: 10.1007/bf02854842
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ketorolac tromethamine 0.5% and levocabastine 0.05%: a multicenter comparison in patients with seasonal allergic conjunctivitis

Abstract: This multicenter, double-masked, randomized, parallel-group study compared the efficacy and safety of ketorolac tromethamine 0.5% ophthalmic solution with levocabastine 0.05% and ketorolac tromethamine vehicle in patients with seasonal allergic conjunctivitis. One drop of ketorolac, levocabastine, or vehicle was instilled in each eye four times daily for 6 weeks. In the majority of efficacy variables, ketorolac produced the greatest improvements, followed by levocabastine and vehicle. Ketorolac was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The anti-inflammatory effects of ketorolac tromethamine in the present report are consistent with the results of previous laboratory studies and the demonstrated clinical efficacy of this drug [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . The effects of ketorolac 0.4% on LPS endotoxin-induced fluorescein leakage in the present study were nearly identical to those produced by ketorolac 0.5% in another study using similar methodology 33 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The anti-inflammatory effects of ketorolac tromethamine in the present report are consistent with the results of previous laboratory studies and the demonstrated clinical efficacy of this drug [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . The effects of ketorolac 0.4% on LPS endotoxin-induced fluorescein leakage in the present study were nearly identical to those produced by ketorolac 0.5% in another study using similar methodology 33 .…”
Section: Discussionsupporting
confidence: 94%
“…Ketorolac tromethamine 0.5% ophthalmic solution (Acular*) has been used for nearly two decades, and has been shown to be safe and effective in the treatment of allergic conjunctivitis, cystoid macular edema, intraoperative miosis, and postoperative ocular inflammation and pain [12][13][14][15][16][17][18][19][20][21][22][23][24] . A lower dose formulation, ketorolac tromethamine 0.4% (Acular LS*), was introduced in 2003 for the treatment of ocular pain, burning, and stinging following refractive surgery 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized, double-masked, multicenter parallel-group study with patients suffering from seasonal allergic conjunctivitis, the efficacy of topical ketorolac 0.5% and levocabastine 0.05% was compared to controls [113]. Ketorolac produced the greatest improvements, however, there was no significant difference to levocabastine.…”
Section: Allergic Conjunctivitismentioning
confidence: 99%
“…The environmental study design has been used to evaluate the anti-allergy effects of several other ophthalmic formulations. [7][8][9] However, this type of study is influenced by environmental factors 10 such as variations in allergy season and weather conditions, high day to day variations in exposure to allergen, and high intersubject variability. In addition, a marked placebo effect of the vehicle eye drops may make it difficult to demonstrate a significant treatment benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant systemic treatments for allergy and any local ocular treatments (including artificial tears or normal saline) other than the trial medication were not permitted during the study. Topical treatments (nasal drops/sprays/ inhalers, oral inhalers) for allergic rhinitis and/or symptomatic asthma were allowed from the follow up visit (days [5][6][7][8] to the study termination visit (days 25-31).…”
Section: Selection Of Study Populationmentioning
confidence: 99%